A mechanism for cancer‐associated inactivation of NQO1 due to P187S and its reactivation by the consensus mutation H80R. Issue 18 (20th August 2017) - Muñoz, Inés G.; Morel, Bertrand; Medina‐Carmona, Encarnación; Pey, Angel L.
Abstract : The cancer‐associated P187S polymorphism in the NAD(P)H:quinone oxidoreductase 1 (NQO1) abolishes enzyme activity by strongly reducing FAD binding affinity. A single mammalian consensus mutation (H80R) protects P187S from inactivation. To provide mechanistic insight into these effects, we report here a detailed structural and thermodynamic characterization of FAD binding to these NQO1 variants. Our results show that H80R causes a population shift in the conformational ensemble of apo‐P187S, remodelling the structure and dynamics of the FAD‐binding site and reducing the energetic penalization arising from the equilibrium between apo‐ and holo‐states. Our analyses illustrate how single amino acid changes can profoundly affect structural and mechanistic features of protein functional traits, with implications for our understanding of protein evolution and human disease. Abstract :